The Role of Open Education and Faculty Gender in Shaping Student Perceptions - Virginia Clinton-Lisell; Alison Kelly (Open Praxis)
Student perceptions of open education, both open educational resources (OER) and open pedagogy, are typically reported as positive in research studies. However, there is a need for controlled research to better understand the specific effects of open education. Furthermore, it is not understood how faculty gender, often noted to be influential in student perceptions of courses, interacts with open education. The current study addressed these issues in a controlled experiment in which college students (N = 413) were randomly assigned to read vignettes of course descriptions that varied based on textbook type (OER or commercial), pedagogy (open or closed), and faculty gender (woman or man). Students who read vignettes with OER reported higher expectancy for success in the course, inherent interest and enjoyment in the course, and personal relevance for the course than those with commercial textbooks. Furthermore, task effort was perceived as lower in courses with OER compared to commercial textbooks. In the vignettes, faculty who used OER were perceived as warmer and more competent than faculty who used commercial textbooks. Students indicated the course would incur greater emotional cost (e.g., stress, anxiety) when it had a professor described as a woman using a commercial textbook compared to an OER. No such difference was noted for the professor described as a man. Overall, the findings indicated that students noticed and perceived the type of textbook (OER or commercial) as an important factor for motivation and professor warmth and competence.